Seminal plasma ascorbic acid level and its relationship to sperm characteristics in Murrah buffalo bulls - MAURYA, S K; SINGH, O P; SRIVASTAVA, SUSHANT (The Indian Journal of Animal Sciences, 2013)
Ascorbic acid levels were investigated in the seminal plasma of Murrah buffalo bulls and its relation was investigated with various parameters of sperm morphology. Semen samples were collected using bovine artificial vagina. Semen volume, sperm concentration, initial motility, livability, sperm abnormality, hypo osmotic swelling, acrosomal integrity and post thaw motility were assessed using standard procedures. Ascorbic acid contents in the seminal plasma were estimated by reverse phase high performance liquid chromatography (RP-HPLC) procedure using UV detection at 254 nm. Bulls were divided into 3 categories depending on the extent of sperm abnormality. The mean ± SEM values of seminal plasma ascorbic acid (mg/ dl) were 4.81 ± 0.08, 3.17 ± 0.09 and 1.79 ± 0.05 in good, medium and poor groups of Murrah buffalo bulls. The seminal plasma ascorbic acid differed significantly in all 3 groups. The seminal plasma ascorbic acid level was positively correlated with spermatozoa with volume/ ejaculate (r2 = 0.710), conc./ ejaculate (r2= 0.915), initial motility (r2 = 0.944), livability (r2 = 0.933), acrosomal integrity (r2 = 0.955), HOS reactiveness (r2 = 0.946) and post-thaw motility (r2 = 0.906); whereas it was negatively correlated with sperm abnormality (r2 = –0.896).